2019
DOI: 10.1186/s12967-019-1975-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinicohistopathological implications of MMP/VEGF expression in retinoblastoma: a combined meta-analysis and bioinformatics analysis

Abstract: Background No in-depth systematic evidence is available for assessing retinoblastoma malignancy and eligibility for subsequent treatment. Methods The Cochrane Library, EMBASE, PubMed, Web of Science, and China Biology Medicine databases were searched, and 16 studies comprising 718 retinoblastoma patients were included. Pooled odds ratios (ORs) and summary correlation coefficients (r) with 95% confidence intervals (CIs) in random-effects, fixed-effects or quality-effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…MMPs are major proteolytic enzymes involved in tumour cell metastasis [47]. The overexpression of MMPs and VEGF can lead to malignant behaviour and are correlated with poor prognosis in many tumours [51][52][53][54]. Accordingly, in our study, we also found that silencing VEGF in NPC cells led to a decrease in N-cadherin, vimentin and MMPs and increase in E-cadherin, suggesting that VEGF can affect metastasis via EMT and MMPs in NPC cells.…”
Section: Discussionsupporting
confidence: 75%
“…MMPs are major proteolytic enzymes involved in tumour cell metastasis [47]. The overexpression of MMPs and VEGF can lead to malignant behaviour and are correlated with poor prognosis in many tumours [51][52][53][54]. Accordingly, in our study, we also found that silencing VEGF in NPC cells led to a decrease in N-cadherin, vimentin and MMPs and increase in E-cadherin, suggesting that VEGF can affect metastasis via EMT and MMPs in NPC cells.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies demonstrated that MMP2/9 are important prognostic factors for various cancers. MMP2 and MMP9 overexpression was associated with poor prognosis in oral cancers [ 12 ], retinoblastoma [ 13 ], bladder cancer [ 14 ], and ovarian epithelial cancer [ 15 ]. The prognostic value of MMP2/9 in BC has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…MMPs are a group of zinc endopeptidases vital for the breakdown of ECM components and basement membrane. Studies have demonstrated that MMP9 is a key prognostic factor for various cancers such as retinoblastoma, bladder cancer, and ovarian epithelial cancer [7][8][9]. In a meta-analysis done by Wei Deng and his colleagues on overexpression of MMPs in Oral cancer patients, have included 15 studies evaluating different types of MMPs concerning 1266 patients.…”
Section: Discussionmentioning
confidence: 99%